Integrated physiological and transcriptomic data revealed the cold-resistant mechanisms in reproductive organs of the ‘Jinguang’ pear cultivar - Sun, Mengying; Lin, Shun; Zhao, Zezhao; Guo, Weizhen; Jiang, Min; Li, Ying; Zhang, Jun; Zhao, Jingxian; Yang, Minsheng (Frontiers in Plant Science, 2025)
The Pyrus spp. (pears) are crucial for the fruit industry; however, low spring temperatures can cause frost damage to their reproductive organs, which poses challenges to the final yields. In this study, we evaluated the response of the flowers and young fruits of the ‘Jinguang’ pear cultivar to low temperatures from integrated phenotypic, physiological, and molecular approaches. We found that the flowers were less sensitive to low temperatures than the young fruits, of which their over-cooling points were −5.6°C and −5.0°C, respectively. Transcriptomic data showed that the differentially expressed genes from flowers and young fruits compared to the control conditions were primarily involved in the biosynthesis of flavonoids, phenylalanine, and tyrosine. Further weighted gene co-expression network analysis uncovered the core transcription factors that may be potentially involved in the pear cold resistance, including MYB20, WRKY53, and WRKY30. Our findings provide valuable insights and candidate gene resources for further exploration of the molecular mechanisms underlying cold resistance in pear trees.